2017
DOI: 10.1002/med.21442
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Targeting of Poly(ADP‐Ribose) Polymerase‐1 (PARP1) in Cancer: Current Developments, Therapeutic Strategies, and Future Opportunities

Abstract: Poly(ADP-ribose) polymerase-1 (PARP-1) plays a central role in numerous cellular processes including DNA repair, replication, and transcription. PARP interacts directly, indirectly or via PARylation with various oncogenic proteins and regulates several transcription factors thereby modulating carcinogenesis. Therapeutic inhibition of PARP is therefore perceived as a promising anticancer strategy and a number of PARP inhibitors (PARPi) are currently under development and clinical evaluation. PARPi inhibit the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 158 publications
0
39
0
Order By: Relevance
“…Interestingly, the role of PARP1 in the regulation of autophagy is controversial. Both autophagy inductor [70][71][72] and inhibitor [73][74][75] role of PARP1 has been described suggesting that the autophagy-modulatory effect of PARylation might show DNA damage and cell type specificity. Even though, we detected an increased number of LC3 puncta, this type of macroautophagy cannot be considered as mitophagy since autophagic puncta show very mild colocalization with mitochondria ( Figure 5D).…”
Section: Parp Inhibition and Uvb Induces Bulk Autophagy But Not Mitopmentioning
confidence: 99%
“…Interestingly, the role of PARP1 in the regulation of autophagy is controversial. Both autophagy inductor [70][71][72] and inhibitor [73][74][75] role of PARP1 has been described suggesting that the autophagy-modulatory effect of PARylation might show DNA damage and cell type specificity. Even though, we detected an increased number of LC3 puncta, this type of macroautophagy cannot be considered as mitophagy since autophagic puncta show very mild colocalization with mitochondria ( Figure 5D).…”
Section: Parp Inhibition and Uvb Induces Bulk Autophagy But Not Mitopmentioning
confidence: 99%
“…However, by showing that continuously active Akt rescued these cells [12], we demonstrated that the said synthetic lethality is predominantly resulted from insufficient Akt activation in ATM suppressed cells. These data emphasize the crucial importance of Akt activation in PARP1 inhibition's cytoprotective property that can lead to undermining PARP1 inhibition's cytostatic effect on breast cancer gene (BRCA) mutations carrying cancers [110]. Independent reports support this notion by demonstrating the increase of PARP1 inhibitors' cytotoxicity by Akt inhibitors [8,11,111].…”
Section: Mechanism Of Parp Inhibition Induced Akt Activationmentioning
confidence: 83%
“…Whilst progress has been made, these inhibitors are not efficient tools for gaining detailed information on the role of PARP1 in cellular responses to DNA insults, due in part to their side effects and interference with other pathways unrelated to PARP1 [33]. Nevertheless, specific PARP inhibitors have been developed for disease treatment in clinics [11,14,15,34,35]. The main knowledge about the biology of PARP1 and PARylation comes from mutagenesis studies of the enzyme using cellular and animal experimental systems.…”
Section: Biological Functions Of Parp1mentioning
confidence: 99%